Analisis Kemampuan Pemecahan Masalah Matematis Ditinjau dari Adversity Quotient (AQ) Siswa Kelas IX SMA Negeri 1 Batuputih - Sabri; Abd. Rahman; Bernard (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2023)
The objective of this study is to characterize the mathematical problem-solving capabilities of 10th grade students at SMA Negeri 1 Batuputih, based on their Adversity Quotient (AQ). This research used a qualitative approach. The subjects in this study consisted of six students of class X SMA Negeri 1 Batuputih who were determined based on AQ criteria with purposive sampling technique. The instruments used were an Adversity Quotient (AQ) questionnaire, a description test, and interview guidelines that had been properly validated by experts. The data collected were analyzed with the stages of data condensation, data presentation, and conclusion drawing and verification. The results showed that: (1) Subjects with climber-type AQ can solve the three stages of problem solving by Polya quite well, namely: the stages of understanding the problem, developing a plan, implementing the plan, however, they have not been able to check the correctness of the results completely; (2) Subjects with camper-type AQ have not been able to understand the problem completely, thus, having difficulty in developing a complete plan; and (3) Subjects with quitter-type AQ cannot understand the problem, and do not have a picture of solving the problem.